Chronic Musculoskeletal Pain is Associated With Depressive Symptoms in Community-Dwelling Older Adults Independent of Physical Activity. Experimental Aging Research - Esposito, Eleonora; Lemes, Italo Ribeiro [UNESP]; Salimei, Paola Sinibaldi; Morelhão, Priscila Kalil [UNESP]; Marques, Larissa Bragança Falcão; Martins, Michael Douglas Silva; Cynthia, Gobbi; Franco, Marcia Rodrigues; Pinto, Rafael Zambelli (Taylor & Francis, 2024)
Background: Prevalence of chronic musculoskeletal pain and depressive symptoms in adults is high; however, whether there is an association between these conditions in older adults is unknown. Objective: The aim of this study was to investigate the association of depressive symptoms with chronic musculoskeletal pain, and specifically with chronic LBP and knee osteoarthritis (OA), in community-dwelling older adults. In addition, we explored whether physical activity can mitigate these associations. Methods: A cross-sectional study design. A cross-sectional study design. Participants recruited were older adults (age ≥60 years) living in the community. Chronic musculoskeletal pain was assessed by specific questions regarding the presence of chronic LBP and knee OA. Depressive symptoms were assessed with the Center for Epidemiologic Studies Depression Scale. Multivariable regression model adjusted for potential confounders (i.e., age, sex, economic status, body composition, and physical activity) was used to investigate the association between chronic musculoskeletal pain and depressive symptoms. Separate analyses were also conducted for older adults with LBP and with knee OA. Results: A total of 509 (69% women) older adults were recruited. The regression analysis showed that musculoskeletal pain was associated with higher depressive symptoms ((Formula presented.) = 2.52, 95% CI: 0.50 to 4.54; p-value <.05) compared with older adults without chronic musculoskeletal pain. Similarly, in the fully adjusted model, which included physical activity, LBP was associated with higher depressive symptoms ((Formula presented.) = 2.80, 95% CI: 0.82 to 4.79; p-value <.01). The association between knee OA and depressive symptoms was not statistically significant after adjusting for physical activity ((Formula presented.) = 2.00, 95% CI: −0.13 to 4.13; p-value =.06). Conclusion: Older adults with chronic musculoskeletal pain have higher depressive symptoms scores, when compared to those without musculoskeletal pain. Physical activity does not seem to influence this association.